1998
DOI: 10.1159/000028189
|View full text |Cite
|
Sign up to set email alerts
|

TRK-530 Inhibits Accumulation of Superoxide Anions Derived from Human Polymorphonuclear Leukocytes and Bone Resorption Induced by Activated Osteoclasts

Abstract: TRK-530, a newly synthesized bisphosphonate, was assessed for its effects on the accumulation of superoxide anions derived from human formyl-methionyl-leucyl-phenylalanine-stimulated polymorphonuclear leukocytes (PMN), and for its effects on bone resorption using a pit formation assay. TRK-530 concentration-dependently inhibited superoxide accumulation derived from PMN and osteoclast pit formation stimulated by 1,25-dihydroxyvitamin D3. Incadronate and risedronate had a strong inhibitory effect on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…In addition to the anticalculogenic effect of TRK-530 in this study, it has also been reported 13,14 to have an anti-inflammatory effect in rat adjuvant arthritis and anti-bone-resorbing activity in systemic administration. The anti-inflammatory and anti-bone resorption effects of this drug suggest that, if facilitated with the mucosal permeability of the gingiva, it may even be effective for inhibiting gingival inflammation and periodontal bone resorption when topically applied.…”
Section: The Anti-inflammatory and Anti-bone Resorption Effects Of Trsupporting
confidence: 67%
See 1 more Smart Citation
“…In addition to the anticalculogenic effect of TRK-530 in this study, it has also been reported 13,14 to have an anti-inflammatory effect in rat adjuvant arthritis and anti-bone-resorbing activity in systemic administration. The anti-inflammatory and anti-bone resorption effects of this drug suggest that, if facilitated with the mucosal permeability of the gingiva, it may even be effective for inhibiting gingival inflammation and periodontal bone resorption when topically applied.…”
Section: The Anti-inflammatory and Anti-bone Resorption Effects Of Trsupporting
confidence: 67%
“…It was also found that TRK-530 has an inhibitory effect on osteoclastic bone resorption. 14 In the field of periodontology, a drug of choice has been sought which would help to eliminate gingival and periodontal inflammation, suppress alveolar bone resorption, and inhibit dental calculus. Since BPs are generally characterized by their physico-chemical inhibitory effects on calciumphosphate crystal formation in vitro, TRK-530 may have an anticalculogenic effect, in addition to its antiinflammatory and anti-bone-resorbing activities.…”
mentioning
confidence: 99%
“…The expression of cyclooxygenase (COX)-2 mRNA and COX-2 protein was also prevented. Since TRK-530 has an anti-oxidant side chain (6) and can inhibit the generation of superoxide anion that reacts with nitric oxide (NO) to form peroxynitrite (ONOO − ), which is known to be a potent stimulator of COX-2 expression, the inhibi- Fig. 4.…”
Section: Inhibitory Effect On the Synthesis Of Pgementioning
confidence: 99%
“…Takizawa, et al reported that whole body administration of MPMBP hindered bone resorption in OVX rats 11) . Additionally, it was reported that in vitro and in vivo examinations showed the suppression of osteoclasts activity 13,14) . Our results showed that the MPMBP suppressed the appearance and differentiation of osteoclasts in the administration site of the MPMBP.…”
Section: Discussionmentioning
confidence: 99%